Interleukin-12 (IL-12) Enhancement of the Cellular Immune Response against Human Immunodeficiency Virus Type 1 Env Antigen in a DNA Prime/Vaccinia Virus Boost Vaccine Regimen Is Time and Dose Dependent: Suppressive Effects of IL-12 Boost Are Mediated by Nitric Oxide - Gherardi, M. Magdalena (American Society for Microbiology, 2000)
We previously demonstrated that codelivery of interleukin-12 (IL-12) with the human immunodeficiency virus type 1 (HIV-1) Env antigen from a recombinant vaccinia virus (rVV) can enhance the specific anti-Env cell-mediated immune (CMI) response. In the present study, we have investigated the effects of IL-12 in mice when it is expressed in a DNA prime/VV boost vaccine regimen. The delivery of IL-12 and Env product during priming with a DNA vector, followed by a booster with VV expressing the Env gene (rVVenv), was found to trigger the optimal CMI response compared with other immunization schedules studied. Significantly, if IL-12 is also delivered as a booster from the viral vector, an impairment of the effects of IL-12 was observed involving nitric oxide (NO), since it was overcome by specific inhibitors of inducible NO synthase. NO caused transient immunosuppression rather than impairment of viral replication. Moreover, at certain viral doses, coadministration of the NO inhibitor during the booster resulted in IL-12-mediated enhancement of the specific CD8(+) T-cell response. In addition, the dose of the IL-12-encoding plasmid (pIL-12) and the route of administration of both vectors were relevant factors for optimal CMI responses. Maximal numbers of Env-specific CD8(+) gamma interferon-secreting cells were obtained when 50 μg of pIL-12 was administered intramuscularly at priming, followed by an intravenous rVVenv boost. Our results demonstrate, in a murine model, critical parameters affecting the success of vaccination schedules based on a combination of DNA and VV vectors in conjunction with immunomodulators.